Angiogenesis stimulated by novel nanoscale bioactive glasses. (25th March 2015) - Mao, Cong; Chen, Xiaofeng; Miao, Guohou; Lin, Cai
Abstract: The ability of biomaterials to induce rapid vascular formation is critical in tissue regeneration. Combining recombinant angiogenic growth factors with bioengineered constructs have proven to be difficult due to several issues, including the instability of recombinant proteins, the need for sustained delivery and the dosage of factors. New formulations of bioactive glass, 58S nanosized bioactive glass (58S-NBG), have been reported to enhance wound healing in animal models better than the first generation of 45S5 Bioglass. Therefore, we investigated the effects of extracts of 58S-NBG and 80S-NBG on cultures of human umbilical vein endothelial cells (HUVECs). Cell viability was assessed by MTS assay. In vitro angiogenesis was measured using an ECM gel tube formation assay, and levels of mRNAs for five angiogenic related genes were measured by qRT-PCR. Extracts of 58S-NBG and 80S-NBG stimulated the proliferation of HUVECs, accelerated cell migration, up-regulated expression of the vascular endothelial growth factor, basic fibroblast growth factor, their receptors, and endothelial nitric oxide synthase, resulting in enhanced tube formation in vitro . The enhanced angiogenic response correlated with increased levels of Ca and Si in the extracts of 58S-NBG and 80S-NBG. The ability of 58S-NBG and 80S-NBG to stimulate angiogenesis in vitro provides alternative approaches for stimulating neovascularization of tissue-engineered constructs.